2021
DOI: 10.3390/jcm10071412
|View full text |Cite
|
Sign up to set email alerts
|

How to Best Exploit Immunotherapeutics in Advanced Gastric Cancer: Between Biomarkers and Novel Cell-Based Approaches

Abstract: Despite extensive research efforts, advanced gastric cancer still has a dismal prognosis with conventional treatment options. Immune checkpoint inhibitors have revolutionized the treatment landscape for many solid tumors. Amongst gastric cancer subtypes, tumors with microsatellite instability and Epstein Barr Virus positive tumors provide the strongest rationale for responding to immunotherapy. Various predictive biomarkers such as mismatch repair status, programmed death ligand 1 expression, tumor mutational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 129 publications
0
6
0
Order By: Relevance
“…Despite intensive investigations towards targeting immune cells, their molecular mediators, and effectors, there is still no established immunotherapeutic strategy for treatment of GC. However, the inhibitors of PD-L1 reached stage 3 clinical trials and demonstrated promising anti-tumor activity in patients with PD-L1-positive GC [ 181 , 182 , 183 ].…”
Section: Therapeutic Targeting Of Nf-κb In Gastric Cancermentioning
confidence: 99%
“…Despite intensive investigations towards targeting immune cells, their molecular mediators, and effectors, there is still no established immunotherapeutic strategy for treatment of GC. However, the inhibitors of PD-L1 reached stage 3 clinical trials and demonstrated promising anti-tumor activity in patients with PD-L1-positive GC [ 181 , 182 , 183 ].…”
Section: Therapeutic Targeting Of Nf-κb In Gastric Cancermentioning
confidence: 99%
“…Recent advances in targeted therapy, such as trastuzumab deruxtecan (T-DXd), have demonstrated significant survival benefits for HER-2 positive advanced gastric cancer [ 23 ]. More recently, immune checkpoint inhibitors have revolutionized the therapy for patients with advanced gastric cancer [ 24 ]. The phase II KEYNOTE-059 trial first evaluated the safety and efficacy of pembrolizumab in patients with metastatic gastric cancer [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite promising options for antibody-based therapies, research on which therapy may be best suited for which patient is still ongoing. Biomarkers that may be used to classify tumors, as well as possibly affect treatment decisions and prognosis, include mismatch repair status, MSI identification, PDL-1 combined positive score (CPS), tumor infiltrating lymphocyte quantification, and tumor mutational burden [ 81 ]. Interestingly, the use of circulating tumor DNA (ctDNA) has the potential to provide data on likelihood of response to ICI and prognosis without requiring a tissue biopsy [ 82 ].…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%